Haggle: A Networking Architecture Designed Around Mobile Users - Scott, James; Hui, Pan; Crowcroft, Jon; Diot, Christophe (Proceedings of the Third Annual IFIP Conference on Wireless On-Demand Network Systems and Services (WONS 2006), 2006)
Current mobile computing applications are infrastructure-centric, due to the IP-based API that these applications are written around. This causes many frustrations for end users, whose needs might be easily met with local connectivity resources but whose applications do not support this (e.g. emailing someone sitting next to you when there is no wireless access point). We identify the general scenario faced by the user of Pocket Switched Networking (PSN), and discuss why the IP-based status quo does not cope well in this environment. We present a set of architectural principles for PSN, and the high-level design of Haggle, our asynchronous, data-centric network architecture which addresses this environment by “raising” the API so that applications can provide the network with application-layer data units (ADUs) with high-level metadata concerning ADU identification, security and delivery to user-named endpoints.